2007
DOI: 10.1002/cm.20242
|View full text |Cite
|
Sign up to set email alerts
|

Myoseverin disrupts sarcomeric organization in myocytes: An effect independent of microtubule assembly inhibition

Abstract: Although disruption of the microtubule (MT) array inhibits myogenesis in myocytes, the relationship between the assembly of microtubules (MT) and the organization of the contractile filaments is not clearly defined. We now report that the assembly of mature myofibrils in hypertrophic cardiac myocytes is disrupted by myoseverin, a compound previously shown to perturb the MT array in skeletal muscle cells. Myoseverin treated cardiac myocytes showed disruptions of the striated Z-bands containing a-actinin and des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Immunofluorescence Confocal Microscopy of NRVM and Heart Sections-NRVM and heart sections (8 m) from PI3K transgenic mice were analyzed by immunofluorescence staining with antibodies to ␣-actinin (Sigma-Aldrich), phalloidin (FITC-conjugates, Molecular Probes), DAPI, and Cy2/Cy3-conjugated secondary antibodies (Chemicon) as described previously (18,22). Prior to staining, hearts from caPI3K, dnPI3K, and Ntg mice were fixed in HistoChoice tissue fixative (Amersco) for 4 h at 4°C and then frozen in Tissue-Tek O.C.T TM compound (Sakura Finetechnical).…”
Section: Methodsmentioning
confidence: 99%
“…Immunofluorescence Confocal Microscopy of NRVM and Heart Sections-NRVM and heart sections (8 m) from PI3K transgenic mice were analyzed by immunofluorescence staining with antibodies to ␣-actinin (Sigma-Aldrich), phalloidin (FITC-conjugates, Molecular Probes), DAPI, and Cy2/Cy3-conjugated secondary antibodies (Chemicon) as described previously (18,22). Prior to staining, hearts from caPI3K, dnPI3K, and Ntg mice were fixed in HistoChoice tissue fixative (Amersco) for 4 h at 4°C and then frozen in Tissue-Tek O.C.T TM compound (Sakura Finetechnical).…”
Section: Methodsmentioning
confidence: 99%
“…The direct participation of microtubules in myofibrillogenesis has been challenged, however, by several groups. For instance, treatment of myoblasts with myoseverin, a drug that depolymerizes microtubules, does affect both myofibrils and microtubules, but upon removal of myoseverin, myofibrils could be formed even in the absence of microtubules [67]. In the conditions used, treatment with nocodazole disassembled microtubules but did not interfere with myofibrils.…”
Section: Microtubulesmentioning
confidence: 99%
“…Microtubule densities (pixels/ m 2 ) were determined by defining cell borders using phalloidin-stained actin filaments as a template. Phalloidin-TRITC staining of contractile filaments was also used to exclude nonmyocytes, which typically exhibit faint, non-striated linear stress fibers with actin staining (27). The defined regions were then transferred to tubulin co-stained images and pixel intensity and cell area (m 2 ) measured (supplemental Fig.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously shown that hypertrophy of these cells is accompanied by an enhanced MT network (27). In this study, we investigated tubulin changes in cardiac myoyctes following 24 h exposure to the ␣-adrenergic agonist phenylephrine (PE) or the IL6 family cytokines, LIF or OSM.…”
Section: Il6 Family Cytokines Induce Mt Stabilization In Cardiac Myocmentioning
confidence: 99%